2018
DOI: 10.1002/jlb.1ri0418-160r
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of T cell aging

Abstract: T cells are a heterogeneous population of cells that differ in their differentiation stages. Functional states are reflected in the epigenome that confers stability in cellular identity and is therefore important for naïve as well as memory T cell function. In many cellular systems, changes in chromatin structure due to alterations in histone expression, histone modifications and DNA methylation are characteristic of the aging process and cause or at least contribute to cellular dysfunction in senescence. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 88 publications
(189 reference statements)
5
35
0
Order By: Relevance
“…Our data on TF networks in naïve CD4 T cells are consistent with the concept that immune aging involves the activation of T‐cell differentiation pathways resulting in a loss of naivety and stemness (Goronzy et al, ). Throughout adult life, the T‐cell compartment is maintained by homeostatic proliferation that is under the control of cytokines as well as requires survival signals from TCR (Goronzy & Weyand, ; Yanes, Gustafson, Weyand, & Goronzy, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our data on TF networks in naïve CD4 T cells are consistent with the concept that immune aging involves the activation of T‐cell differentiation pathways resulting in a loss of naivety and stemness (Goronzy et al, ). Throughout adult life, the T‐cell compartment is maintained by homeostatic proliferation that is under the control of cytokines as well as requires survival signals from TCR (Goronzy & Weyand, ; Yanes, Gustafson, Weyand, & Goronzy, ).…”
Section: Discussionsupporting
confidence: 89%
“…Epigenetic studies of human CD8 T cells have provided evidence for loss of stemness as indicated by increased accessibility for bZIP transcription factors with age, a signature that is also a hallmark of differentiation (Moskowitz et al, ; Ucar et al, ). A similar but less pronounced trend is seen for naïve CD4 T cells (Goronzy, Hu, Kim, Jadhav, & Weyand, ). T‐cell phenotypic changes indicating an altered composition with age include the loss of CD31, CR1, and CR2 and the gain of CD25 in subsets of naïve CD4 T cells (den Braber et al, ; Kohler & Thiel, ; Pekalski et al, ).…”
Section: Introductionsupporting
confidence: 58%
“…Loss of polyfunctionality may be a consequence of more progressed or end-differentiation, as indicated by the chromatin state of old central memory T cells or the increased frequencies of terminally differentiated effector memory cells (TEMRAs). 130 An alternative explanation is that memory T cells in older individuals respond qualitatively differently to TCR stimulation than in young. Indeed, similar to naive T cells, memory CD8 T cells display reduced miR-181a, which likely reduces some TCRmediated signals.…”
Section: Aging Tissue Microenvironment As a Blockade To Effective Primentioning
confidence: 99%
“…With the exception of these effector T cells that are frequently specific for latent viruses, unstimulated circulating naïve and memory CD4 + and CD8 + T cells do not show evidence of cellular senescence that could account for age-associated immune defects (8). Rather than senescence-associated defects, epigenetic signatures and microRNA profiles induced by T cell aging are indicative of activated differentiation pathways that favor development into short-lived effector cells (9).…”
Section: Introductionmentioning
confidence: 99%